Mortality from systemic lúpus erythematosus in Brazil: analysis of the sociodemographic profile (Research, Society and Development, 2022)
Systemic Lupus Erythematosus (SLE) is a chronic inflammatory autoimmune disease that presents with symptoms such as fever, weight loss, loss of appetite, weakness and discouragement. Therefore, the study aimed to analyze the profile of SLE in Brazil, from 2010 to 2019. This is a descriptive, epidemiological, exploratory and cross-sectional study, with a quantitative approach, of deaths from SLE reported in the Department of Informatics of the Unified System of Health of Brazil (DATASUS). Data were analyzed in Excel 2010. 10030 cases of death from SLE were reported between 2010 and 2019, with the Southeast region with the highest number of cases (4255 cases) followed by the Northeast (2473 cases). Regarding the profile, there were more deaths in females, with a percentage above 86% for all regions of the country. As for race, in the North, Northeast and Midwest regions, the highest percentage was recorded in the Brown racial group (North - 71.44%; Northeast - 59.28% and Midwest - 50.72%), as for the age group , in the North region, the age between 20 and 29 years was more frequent, corresponding to 25.34% of the cases. In the Northeast and Midwest regions, the age group from 30 to 39 years was more frequent, referring to the percentages of 22.68% and 21.88% respectively. As for education, the patients had, more frequently, from 8 to 11 years of schooling (North - 35.87%; Northeast - 26.85%; Midwest - 30.67%; Southeast 30.3%; and South – 30.12%). The Northeast region presents a smaller quantity of deaths, in relation to the other regions, being predominant in women, of brown color, aged between 31 and 39 years old.